Orbital Angular Momentum (OAM) of Rotating Modes Driven by Electrons in Electron Cyclotron Masers - Ashwini Sawant; Mun Seok Choe; Manfred Thumm; EunMi Choi (Scientific Reports, 2017)
Abstract The well-defined orbital angular momentum (OAM) of rotating cavity modes operating near the cutoff frequency excited by gyrating electrons in a high-power electron cyclotron maser (ECM)—a gyrotron—has been derived by photonic and electromagnetic wave approaches. A mode generator was built with a high-precision 3D printing technique to mimic the rotating gyrotron modes for precise low-power measurements and shows clear natural production of higher-order OAM modes. Cold-test measurements of higher-order OAM mode generation promise the realization towards wireless long-range communications using high-power ECMs.